KONSENTRASI ASAP CAIR (Liquid Smoke) DAN WAKTU PERENDAMAN TERHADAP KUALITAS DAGING AYAM BROILER - Sadjadi; Ririn Novita Sari; Teguh Karyono; Zulhapi Utama Adlan (JURNAL PETERNAKAN SILAMPARI (JPS) ISSN: 2089-4791, 2023)
This study aims to determine the concentration of liquid smoke (Liqiud Smoke) and immersion time on the quality of broiler chicken meat. This study used an experimental method with a completely randomized design (CRD) with a factorial pattern, 2 factors consisting of 4 treatments of liquid smoke concentration each and 3 treatments of immersion time with 3 replications. The treatment factors are as follows: A0 = meat + 0% liquid smoke, A1 = meat + 4% liquid smoke, A2 = meat + 8% liquid smoke, A3 = meat + 12% liquid smoke. Parameters observed in this study were water holding capacity, fat content, cooking loss, pH. By using analysis of variance and further test BNJ. The results of this study indicate that the addition of liquid smoke concentration and immersion time has a significant effect (P<0.05) on fat content and pH. No significant effect (P>0.05) on water holding capacity and cooking loss. Based on the results of the research on the concentration of liquid smoke (liquid smoke) and immersion time on the quality of broiler chicken meat, it can be concluded that treatment A2W2 (Immerison 30 Minutes and concentration of liquid smoke 8ml) gave the best effect on pH and water holding capacity